Waste truck-tyre processing by flash pyrolysis in a conical spouted bed reactor. (15th June 2017) - Lopez, G.; Alvarez, J.; Amutio, M.; Mkhize, N.M.; Danon, B.; van der Gryp, P.; Görgens, J.F.; Bilbao, J.; Olazar, M.
Highlights: Flash pyrolysis improves TPO and limonene yields vs. slow pyrolysis. The most suitable temperature for TPO and limonene maximization was 475 °C. Operating at 575 °C gas yields and char quality was enhanced. Temperature showed a limited effect on sulphur distribution among products. Abstract: The flash pyrolysis of waste truck-tyres was studied in a conical spouted bed reactor (CSBR) operating in continuous regime. The influence of temperature on product distribution was analysed in the 425–575 °C range. A detailed characterization of the pyrolysis products was carried out in order to assess their most feasible application. Moreover, special attention was paid to the sulphur distribution among the products. The analysis of gaseous products was carried out using a micro-GC and the tyre pyrolysis oil (TPO) by means of GC-FID using peak areas for quantification, with GC/MS for identification and elemental analysis. Finally, the char was subjected to elemental analysis and surface characterization. According to the results, 475 °C is an appropriate temperature for the pyrolysis of waste tyres, given that it ensures total devolatilisation of tyre rubber and a high TPO yield, 58.2 wt.%. Moreover, the quality of the oil is optimum at this temperature, especially in terms of high concentrations of valuable chemicals, such as limonene. An increase in temperature to 575 °C reduced the TPO yield to 53.9 wt.% and substantially changed its chemical composition by increasing the aromatic content. However, the quality of the recovered char was improved at high temperatures.